Development of a new method for ATFCM based on trajectory-based operations - Gatsinzi, Dany; Saez Nieto, Francisco Javier; Madani, Irfan (SAGE, 2017)
This paper discusses a possibility to evolve the current Air Traffic Flow and Capacity Management towards a more proactive approach. This new method focuses on reducing the expected probability of air traffic control intervention based on “hot spot” identification and mitigation at strategic level by applying subliminal changes on the times of arrival at the crossing or merging points (junctions). The concept is fully aligned with the trajectory-based operation principles. The approach assumes that the changes on the times of arrival only demand small speed changes from the involved aircraft. In this study, the hot spots are defined as clusters of aircraft expected to arrive to the junctions. Two aircraft are said to be in the same cluster if their proximity and closure rate are below a given threshold. Some exercises are proposed and solved by applying this method. The obtained results show its ability to remove the potential conflicts by applying simple linear programming. This approach seeks to change the current capacity limiting factor, established by the number of aircraft occupying simultaneously each sector, to another parameter where the level of traffic complexity, flowing towards junctions, is identified and mitigated at strategic level. The speed changes, used as the control variable and computed before or during the flight, are designed to provide an adjustment on aircraft’s required time of arrival at the junctions in order to have a de-randomised and well-behaved (conflict free) traffic. This will enable improvements in airspace capacity/ safety binomial. It is recognised that this measure alone is unable to produce a conflict free airspace, and then other collaborative and coordinated actions, such as adjusting and swapping departing times at the departing airports (before the aircraft are taking off), offsetting some flights from nominal route, and allowing multi-agent separation management (while they are in flight) should be applied together with this method.
Keywords: Air traffic flow and capacity management; Trajectory-based operation; Conflict detection and resolutions; Demand capacity balancing; Junction; Time of arrival; Hot spot; Complexity